77 Shadow Street : a novel - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2011)
Once the center of madness, suicide, mass murder, and whispers of things far worse, the 1800s Gilded Age palace known as the Pendleton, has been re-christened in the 1970s as a luxury apartment building. But now inexplicable shadows caper across walls, security cameras relay impossible images, phantom voices mutter in strange tongues, not-quite-human figures lurk in the basement, and elevators plunge into unknown depths.
Keywords: Haunted places -- Fiction; Paranormal fiction; Parapsychology -- Fiction; Mystery fiction; Horror fiction; Suspense fiction